Socio-health and physical vulnerability of child labourers in farming communities of Southwest Nigeria" (2016)
In traditional farming communities of Southwest Nigeria, the distinction between child labour and socialization into adult and normative roles was difficult to establish. As societies and patterns of relationships signalled increasing complexity, the differences became evident. This qualitative study investigated the social, economic, health and physical vulnerability of children engaged in labourious cocoa farming activities in selected communities of Southwest Nigeria. Employing Structural Functionalism and Ethno-methodology as theoretical perspectives, findings reveal contextual differences both in perception and existence of child labour in selected study locations. Although the incidence of child labour in cocoa farming has waned markedly in the area compared to what obtained several years earlier, individual and household socioeconomic empowerment is a critical factor for positive attitudinal and behavioural change. This will go a long way to redefining the dynamics and extent to which children can be involved in cocoa farming.